Tuvalu Rapid eTrade Readiness Assessment - United Nations Conference on Trade; Development (United Nations, 2020)
The eTrade Readiness Assessment of Tuvalu focuses on examining seven key policy areas that are most relevant for e-commerce. Within each area, critical readiness gaps are identified and relevant recommendations are proposed to overcome barriers and bottlenecks to the growth of digital trade. The Tuvalu Rapid eTrade Readiness Assessment is the nineteenth such assessment conducted by UNCTAD since the launch of the Programme in 2017. There are signs that Tuvalu has started to consider some of the potential benefits that e-commerce can bring to its population and in particular in reducing some of the negative effects of its geographic location and small size. For this to happen, existing policies such as TKIII and TPF must be implemented, while higher visibility of the digital economy in the national development agenda constitutes a necessary pre-condition to tackle all the aforementioned challenges. This Rapid eTrade Readiness Assessment helps identify opportunities and barriers for Tuvalu to engage in and benefit from e-commerce and the digital economy. It also helps operationalize relevant strategies included in the Tuvalu's Trade Policy Statement and the Tuvalu Private Sector Development Plan. Both documents highlight agriculture, fisheries, tourism and labor mobility as key areas of export growth, all of which could be supported by e-commerce. They also note other important cross-cutting areas that are relevant to e-commerce, including competition policy and consumer protection, public procurement, intellectual property rights, and gender issues.